WORDWALL-BASED BRAINSTORMING LEARNING MODEL: AN EXPERIMENTAL STUDY ON STUDENTS’ ABILITY TO EXPRESS IDEAS AS AN INDICATOR OF ACTIVE LEARNING - Ridho Azzam Al Faruq; Sa’idy Sa’idy; Ida Faridatul Hasanah; Baharudin Baharudin (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This article aims to determine the effectiveness of applying the Wordwall interactive game-assisted brainstorming learning model in increasing student learning activity, particularly in terms of the ability to express ideas. The study used a quantitative approach with a quasi-experimental design. The research subjects were seventh-grade students at SMP Negeri 22 Bandar Lampung, who were divided into an experimental class and a control class. The instrument used was a learning activity questionnaire that had been tested for validity and reliability. Data analysis was performed through normality tests, homogeneity tests, Mann-Whitney U tests, and t-tests. The results showed a significant difference between the learning activities of students in the experimental class and the control class with a significance value of < 0.05. Thus, the application of the Wordwall-assisted brainstorming learning model proved to be effective in increasing student learning activeness, especially in terms of courage and fluency in expressing ideas. This model is relevant to be applied as an alternative to innovative learning in the context of 21st-century learning.